Existence of positive solutions in the space of Hölder functions for a class of nonlinear fractional differential equations with integral boundary conditions - Caballero, Josefa; Harjani, Jackie; López, Belén; Sadarangani, Kishin (Topological Methods in Nonlinear Analysis, 2024)
We study the existence of positive solutions for a fractional differential equation with integral boundary conditions. Our solutions are placed in the spaceof Hölder functions and the main tools used in the proof of the results are the classical Schauder fixed point theorem and a sufficient condition about the relative compactness in Hölder spaces. Moreover, some examples are shown illustrating the results.